Rare NOTCH3 Variants in a Chinese Population-Based Cohort and Its Relationship With Cerebral Small Vessel Disease. Issue 12 (18th August 2021) - Liu, Jing-Yi; Yao, Ming; Dai, Yi; Han, Fei; Zhai, Fei-Fei; Zhang, Ding-Ding; Zhou, Li-Xin; Ni, Jun; Zhang, Shu-Yang; Cui, Li-Ying; Zhu, Yi-Cheng
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Researches on rare variants of NOTCH3 in the general Chinese population are lacking. This study aims to describe the spectrum of rare NOTCH3 variants by whole-exome sequencing in a Chinese community-based cohort and to investigate the association between rare NOTCH3 variants and age-related cerebral small vessel disease. Methods: The cross-sectional study comprised 1065 participants who underwent whole-exome sequencing and brain magnetic resonance imaging. NOTCH3 variants with minor allele frequency<1% in all 4 public population databases (1000 Genomes, ESP6500siv2_ALL, GnomAD_ALL, and GnomAD_EAS) were defined as rare variants. Multivariable linear and logistic regressions were used to investigate the associations between rare NOTCH3 variants and volume of white matter hyperintensities and cerebral small vessel disease burden. Clinical and imaging characteristics of rare NOTCH3 variant carriers were summarized. Results: Sixty-five rare NOTCH3 variants were identified in 147 of 1065 (13.8%) participants, including 57 missense single nucleotide polymorphisms (SNPs), 5 SNPs in splice branching sites, and 3 frameshift deletions. A significantly higher volume of white matter hyperintensities and heavier burden of cerebral small vessel disease was found in carriers of rare NOTCH3 EGFr (epidermal growth factor-like repeats)-involving variants, but not in carriers of EGFr-sparing variants. The carrying rate of rare EGFr-involving NOTCH3 variants in participants with dementia or stroke was significantly higher than those without dementia or stroke (12.4% versus 6.6%, P =0.041). Magnetic resonance imaging signs suggestive of CADASIL were found in 3.4% (5/145) rare EGFr cysteine-sparing NOTCH3 variant carriers but not in 2 cysteine-altering NOTCH3 variant carriers. Conclusions: Carriers of rare NOTCH3 variants involving the EGFr domain may be genetically predisposed to age-related cerebral small vessel disease in the general Chinese population.